2020
DOI: 10.1002/clc.23398
|View full text |Cite
|
Sign up to set email alerts
|

Impact of body mass index on procedural complications, procedure duration, and radiation dose in patients with atrial fibrillation undergoing radiofrequency ablation: A systematic review and meta‐analysis

Abstract: Background: The association of body mass index (BMI) and procedure-related factors in patients with atrial fibrillation (AF) after radiofrequency ablation (RFA) is still unclear. Hypothesis: BMI is associated with increased the radiation dose, procedure duration, and procedural complications. Methods: Prospective studies assessing BMI and procedure duration, radiation dose, and procedural complications in patients with AF after RFA were identified through electronic searches of PubMed, Embase, and the Cochrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 33 publications
2
10
0
1
Order By: Relevance
“…Moreover, obese patients undergoing general anesthesia or conscious sedation during this relatively lengthy procedure may experience higher rates of respiratory complications related to worse respiratory mechanics. 35 Obese patients have been shown to have significantly longer procedural duration than non‐obese patients in a meta‐analysis, 18 possibly contributing to respiratory complications. The higher costs associated with obesity may be indicative of differences in anesthesia approaches (more general anesthesia rather than sedation) and not just hospital stay and complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, obese patients undergoing general anesthesia or conscious sedation during this relatively lengthy procedure may experience higher rates of respiratory complications related to worse respiratory mechanics. 35 Obese patients have been shown to have significantly longer procedural duration than non‐obese patients in a meta‐analysis, 18 possibly contributing to respiratory complications. The higher costs associated with obesity may be indicative of differences in anesthesia approaches (more general anesthesia rather than sedation) and not just hospital stay and complications.…”
Section: Discussionmentioning
confidence: 99%
“…Others have shown that risk factor modification reduces the risk of incident and recurrent AF 16,17 . In terms of procedural complications, meta‐analyses of AF ablation data in obese and diabetic patients primarily from specialized centers have shown comparable rates to non‐obese and non‐diabetic patients 18,19 . However, the real‐world rate of adverse in‐hospital ablation outcomes in obese and diabetic patients remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to patients with neither comorbidity, those with either obesity, diabetes or both had higher rates of chronic diseases and a higher proportion had their ablation performed at low-volume centers. 18.8% (N = 2315) in 2013 (p < 0.001). There was a dip in the total number of captured ablations after 2011, likely due to the increased labeling of some of these procedures as outpatient.…”
Section: Resultsmentioning
confidence: 94%
“…Moreover, obese patients undergoing general anesthesia or conscious sedation during this relatively lengthy procedure may experience higher rates of respiratory complications related to worse respiratory mechanics 32 . Obese patients have been shown to have signi cantly longer procedural duration than non-obese patients in a meta-analysis 18 , possibly contributing to respiratory complications. The higher costs associated with obesity may be indicative of differences in anesthesia approaches (more general anesthesia rather than sedation) and not just hospital stay and complications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation